PENGARUH KECERDASAN LOGIS-MATEMATIS DAN KECERDASAN MUSIKAL TERHADAP HIGHER ORDER THINKING SKILLS (HOTS) - Leonard Leonard; Nanda Novi Linda (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2018)
The aim of this study is to test the hypothesis about the influence of logical-mathematical intelligence to higher order thinking skills. The method that used in this research is survey method. This research using descriptive analysis and data requirement test (normality test, regression linearity test, and multicollinearity test), followed by hypothesis testing using correlation and multiple regression. The samples of research are taken from an affordable population by removing data outliers. The number of samples after the data outliers were eliminated were 99 students SMPN 6 Bekasi VIII grader. Instruments that used is a multiple choice test sheet to measure logical-mathematical intelligence, straight observation sheet to measure musical intelligence, and test sheet problem essay to measure higher order thinking skills. The results of hypothesis testing were obtained by following conclusions: 1) There is a positive influence that significant in logical-mathematical intelligence and musical intelligence to higher order thinking skills. 2) There is a positive influence that significant in logical-mathematical intelligence to higher order thinking skills. 3) There is no positive influence that significant in musical intelligence to higher order thinking skills.